ORGN 511-Total synthesis of 7-chloro-10-methoxycamptothecin: an important synthon for commercially important derivatives of camptothecin - Sharma, Anil; Chavan, Subhash P.; Venkatraman, M. S. (Abstracts of Papers of the American Chemical Society, 2008)
235th American-Chemical-Society National Meeting, New Orleans, LA, APR 06-10, 2008

Organocatalytic enantioselective synthesis of beta-blockers: (S)-propranolol and (S)-naftopidil - Panchgalle, Sharad P.; Gore, Rohitkumar G.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2009)
An efficient enantioselective synthesis of beta-adrenergic blockers (S)-propranolol and (S)-naftopidil with > 98% ee using an L-proline-catalyzed alpha-aminoxylation of an aldehyde as a key step is described. (c) 2009 Elsevier Ltd. All rights reserved.

Organocatalytic asymmetric synthesis of (-)-delta-coniceine based on sequential proline-catalyzed asymmetric alpha-amination-HWE olefination - Panchgalle, Sharad P.; Bidwai, Harshad B.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2010)
An efficient asymmetric synthesis of (-)-delta-coniceine via sequential proline-catalyzed asymmetric alpha-amination and Horner-Wadsworth-Emmons olefination of an aldehyde with excellent enantiomeric excess (>99%) and high yields (overall yield 44%) is described. (C) 2010 Elsevier Ltd. All rights reserved.

One-step synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines and their use in the synthesis of highly functionalized 2,3,5,6,7-and 2,3,4,5,7-substituted indoles - Sawargave, Sangmeshwer P.; Kudale, Ananada S.; Deore, Jaydeep V.; Bhosale, Dattatry S.; Divse, Jaisingh M.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2011)
A three-component, one-step method for the synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines involving reaction of alkyl aldehyde, malononitrile and aryl aldehyde in presence of morpholine is reported. Highly functionalized 2,3,5,6,7- and 2,3,4,5,7-substituted indoles were prepared from these dicyanoanilines by reaction with ethyl bromoacetate. These substituted dicyanoanilines and indoles have a potential to be converted into various other compounds taking advantage of various functional groups present in these molecules. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Dicyanoanilines; indoles; Malononitrile

One-pot migration-formylation of benzyl aryl ethers under duff reaction condition - Chavan, Subhash P.; Lasonkar, Pradeep B. (Tetrahedron Letters, 2013)
A one-pot migration-formylation of benzyl aryl ethers under Duff reaction condition is described. The reaction was performed with HMTA (hexamethylene tetramine) and TFA (trifluoroacetic acid). Under the optimal reaction conditions, a variety of Bn and PMB ethers underwent ortho rearrangement. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzyl aryl ethers; Duff reaction; Hexamethylene tetramine; One-pot; ortho Rearrangement

One-step method for the synthesis of aryl olefins from aryl aldehydes and aliphatic aldehydes - Borate, Hanumant B.; Gaikwad, Supriya H.; Kudale, Ananada S.; Chavan, Subhash P.; Pharande, Shrikant G.; Wagh, Vitthal D.; Sawant, Vikram S. (Tetrahedron Letters, 2013)
A conceptually new one-step reaction affording unexpected aryl olefinic product from aromatic aldehyde, aliphatic aldehyde and malononitrile in the presence of acetic acid-ammonium acetate under mild reaction conditions without using any metal catalyst is reported. This novel reaction was used to prepare a number of substituted aryl olefins including new molecules. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Aliphatic aldehyde; Aromatic aldehyde; Aryl olefin; Dicyanoaniline; Malononitrile